The Indian Plate subducting below the Tibet Plateau is tearing apart - Lin Liu; Danian Shi; Simon L. Klemperer (Communications Earth & Environment)
Abstract The first-order configuration of the Himalayan orogen is defined by northward motion of the Indian plate, whether directly underplating Tibetan crust or subducting beneath a mantle wedge. Here we used 3D S-wave receiver-functions from 462 seismic stations across southern Tibet and show orogen-perpendicular tearing of the Indian plate. West of 90°E, the southern limit of the Tibetan lithosphere-asthenosphere boundary is at the Indian crustal front, ~100-km north of the Yarlung-Zangbo suture, implying underplating of intact Indian lithosphere beneath Tibet. Further east, Indian lithospheric mantle delaminates from Indian crust, likely by gravitationally-induced rollback, separated from Indian crust by a wedge of asthenosphere between Indian crust and Indian mantle lithosphere. Nascent Tibetan lithosphere and its subjacent thin asthenosphere continue to ~100 km south of the Yarlung-Zangbo suture. This contrast in lithospheric structures at 90–92°E (across the Yadong-Gulu and Cona-Sangri rifts), in agreement with helium isotopes and intermediate-depth earthquakes, suggests the subducting Indian plate is torn along the convergence direction.